TEACHERS’ ROLE TOWARDS STUDENTS’ ACHIEVEMENT IN ENGLISH DEBATE COMPETITION - Jumharia Djamereng (UIN Alauddin Makassar, 2018)
The research is qualitative research that intends to describe the factors that influence the students’ achievement in debate competition English Got Talent. Therefore, it was formulated the problem statement as follows: 1) Which factors that influence the students’ achievement in debate competition? 2) How are the competences of English teachers of SMUN 1 and SMUN 3 in teaching and guiding English subject in both schools? To fulfill data collection, primary data were taken from 5 teachers from every schools so the total number were 10 teachers. While the secondary data also were 10 students who were taken from 5 students from every school. The technique in collecting data were interview and observation. The result of the research shows that factors that may cause the students of SMUN 3 and SMUN 1 get achievement in debate competition, such as; the competencies owned by teachers from both schools who some of them have S1 degree in English Education and some others are Magister in English Education. Besides, they actively develop their skills in teaching methods by joining seminars and workshops. Therefore they were more creative in presenting the materials by using various teaching strategies that may help and support the students in English learning process. They also give attention to the teaching material which not too emphasize on using English book provided by the school. In opposites, they were selective in using the teaching material, some of them develop the material by their own selves which taken from commercial books and internet. Over all, other factor that may also contribute to their achievement are the existences of teacher that becomes supervisor who responsible to prepare the students to join the competition. They have been being consulted and guided since the X years and it is usually given for 3 months before the competition held. Therefore it makes them are very well prepared to join the competition.